2018
DOI: 10.1002/14651858.cd009103.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for improving modifiable risk factor control in the secondary prevention of stroke

Abstract: Analysis 2.2. Comparison 2 Organisational interventions versus usual care, Outcome 2 Mean diastolic blood pressure. Analysis 2.3. Comparison 2 Organisational interventions versus usual care, Outcome 3 Blood pressure target achievement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
76
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(85 citation statements)
references
References 197 publications
3
76
0
3
Order By: Relevance
“…Así mismo, a pesar del conocimiento sobre el ACV, la presencia de los comportamientos de riesgo, da indicios de sub-valorización. Estos resultados van al encuentro de estudio de revisión, donde se encuentran resultados mixtos de la eficacia de las intervenciones educativas, con variaciones según los diferentes factores (24) . La posibilidad de tratamiento del ACV es desconocida por la mayoría de los participantes, hecho indicado anteriormente (20) , pero la posibilidad de cura puede incitar, la necesidad de aprender como asistir a personas con ACV en evolución.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Así mismo, a pesar del conocimiento sobre el ACV, la presencia de los comportamientos de riesgo, da indicios de sub-valorización. Estos resultados van al encuentro de estudio de revisión, donde se encuentran resultados mixtos de la eficacia de las intervenciones educativas, con variaciones según los diferentes factores (24) . La posibilidad de tratamiento del ACV es desconocida por la mayoría de los participantes, hecho indicado anteriormente (20) , pero la posibilidad de cura puede incitar, la necesidad de aprender como asistir a personas con ACV en evolución.…”
Section: Discussionunclassified
“…El único momento, de recogida de datos, impide el seguimiento de los participantes. La utilización de medidas estandarizadas es también una fragilidad del estudio actual, reconocida en revisión de literatura (24,27) .…”
Section: Discussionunclassified
“…Auf Grund dieser hohen Verbreitung scheint die Verwendung von mHealth eine geeignete Strategie sowohl zur primären als auch zur sekundären Prävention von Schlaganfall, wobei der Fokus dieser Arbeit auf der Sekundärprävention liegt. Primärprävention bedeutet in diesem Kontext Vorbeugung eines Schlaganfalls, während sich die Sekundärprävention auf die Verhinderung eines weiteren Schlaganfalls bezieht [8][9][10][11]…”
Section: Use Of Smartphone Apps In Secondary Stroke Prevention Einleiunclassified
“…[2][3][4] These studies have demonstrated accumulative scienti c evidence showing that stroke is associated with modi able risk factors, such as high blood pressure, obesity, high cholesterol, and health behavioral risk factors such as smoking, sleep deprivation and sedentary lifestyle. [5][6][7][8] There are also remarkable disparities, with higher stroke incidence and prevalence found among older population, Blacks and those with low socioeconomic status. 9 In comparison, few studies have examined the mechanisms between neighborhood characteristics and neighborhood-level prevalence of stroke, despite the growing awareness that individuals' health is closely related to the neighborhood environment they live in.…”
Section: Introductionmentioning
confidence: 99%
“…These factors have been linked to cardiovascular health outcomes at the individual patient level, and can be grouped into four major domains, unhealthy behaviors, prevention measures, sociodemographic indicators and environmental measures. 5,6,8,9 We then exploited quantile regression random forests (QRFs) -a machine learning modeling technique -to rank the relative importance of the potential predictors, and proposed and implemented an algorithm to identify a set of major determinants for the distribution of neighborhood-level prevalence of stroke. We further compared the performance of our machine learning method to the performance of regression approaches commonly used in practice.…”
Section: Introductionmentioning
confidence: 99%